Long anatomical femoral stem reduces stress concentrations on femurs with lateral bowing deformity: A finite element analysis (Annals of Medical Research, 2021)
Aim: Femoral morphology varies widely among different ages and sexes. Lateral bowing is a variance of the femur described in elderly females from Asian race. This bowing deformity is usually underestimated in patient evaluation and planning the most suitable treatment. In this study we aimed to evaluate the stress distribution around femoral prosthesis in femurs with lateral bowing deformity, using a finite-element (FE) method. The main objective of our study was to compare stress concentrations around five different stem models.Material and Methods: A lateral femoral bowing deformity model was obtained from the post-operative CT data of a 69-year-old woman, using a software (3D-Slicer). Straight and anatomical femoral stem models with different lengths are designed on the model of von Mises stress concentrations of five different stem models are evaluated.Results: The long anatomic stem did not lead to excessive stress concentrations on any area of the femur and a uniform stress distribution was obtained. The maximum von Mises stress for long anatomical stem (29,197 MPa) was lower than any other model. Highest stress concentrations were observed in medium straight stems (43,147 MPa).Conclusion: For patients with a lateral bowing deformity, longer anatomical femoral stems may overcome the excessive stress shielding, providing stress distribution over a wider region of the femur.Keywords: Femoral Lateral Bowing; Finite Element; Anatomical Stem; Hip Arthroplasty.